A methodology for optimizing treatment head angle arrangement for multi-angle FLASH intensity modulated radiation therapy platforms - Cui, Weijie; Guo, Chenlei; Hu, Zhihui; Wang, Yunxiang; Men, Kuo; Dai, Jianrong (Frontiers in Oncology, 2025)
PurposeFlash therapy technology has been introduced, and several systems have been developed for its implementation. One such FLASH radiotherapy platform employs multiple treatment heads that deliver radiation to a target simultaneously. However, the optimal number of treatment heads and their precise angular configuration needed to best meet clinical requirements remain to be determined.Methods and materialsIn this study, each treatment head angle is treated as an independent variable, and the total angular discrepancy between a set of beam directions from clinically used plans and those generated by a virtual FLASH radiotherapy platform is defined as the objective function. This problem is solved using an optimization technique known as Adaptive Simulated Annealing (ASA). The performance of the proposed optimization model was evaluated using a dataset of 69,928 beams from 8,866 intensity-modulated radiation therapy (IMRT) plans collected over a two-year period in our department. These plans represent various types of common tumors, including nasopharyngeal, breast, esophageal, lung, and rectal cancers. The total angular discrepancy was compared between the beam directions obtained through the optimized treatment head arrangement and the directions used in clinical practice.ResultsFor a virtual FLASH therapy platform equipped with five treatment heads, we obtained the optimized treatment head angle arrangements both with and without the constraint of an imaging system. Under the imaging system constraint, the optimized angles were 0°, 40.4°, 169.4°, 201.2°, and 239.8°, resulting in an average discrepancy of 38.9°compared to the beam directions used in the reference treatment plan cohort. Without the imaging system constraint, the optimized angles were 0°, 155.4°, 234.4°, 266.2°, and 304.8°, yielding an average discrepancy of 37.8°. In contrast, equally spaced treatment head angles produced an average discrepancy of 78.4°.ConclusionA methodology for optimizing the treatment head angle arrangement for multi-angle FLASH radiotherapy platforms is proposed. The optimized configuration provides an effective solution for clinical applications, balancing performance with practical feasibility.